Implementation Learning Organization in Realizing Child-Friendly Madrasas in Madrasah Aliyah Bandung Regency - Sopian, Asep; Ruswandi, Uus; Sarbini, Ahmad; Hafid, Hafid (Lafadz Jaya Publisher, 2025)
Problems surrounding child discrimination are increasingly emerging in society's social life. The rise in cases of immorality, violence and bullying against children is a strong reason for the importance of protecting children's rights. This is because the presence of children often becomes an outlet for violence, whether at home, school or in the environment. The aim of this research is to determine the implementation of learning organizations in creating child-friendly madrasas in Madrasah Aliyah Bandung Regency. The approach to this research uses a qualitative approach. The research method used in this research is a qualitative descriptive method. This data analysis activity refers to theoretical references related to research problems, namely by taking the same information from various informants who are known to have an honest and open nature to reveal data related to the implementation of learning organizations in realizing child-friendly madrasas. The research results show that the implementation of Learning Organization (LO) at MAN 1 Bandung and MAN 2 Bandung has had a significant impact in realizing child-friendly madrasas. Through the Learning Organization (LO), the two madrasas can create a culture of sustainable learning, where all elements of the madrasah community, teachers, students, staff, parents and the community, are actively involved in the learning, evaluation and improvement process.